Rapid transformation in aquatic food value chains in three Nigerian states - Liverpool-Tasie, Lenis Saweda O.; Wineman, Ayala; Amadi, Mark Umunna; Gona, Ayuba; Emenekwe, Chukwuemeka Chinonso; Fang, Ming; Olunuga, Olawale; Onyeneke, Robert Ugochukwu; Norbert, Sunday; Adenike, Taiwo Mayomi; Reardon, Thomas; Belton, Ben (Frontiers Media, 2024)
Introduction: Nigeria is Africa’s most populous country, third largest fish producer, and second largest aquaculture producer. There have been numerous studies of aquaculture and fisheries in Nigeria, but no study to date has analyzed aquaculture and capture fisheries value chains together, while giving equal weight to all value chain segments and systematically capturing information on temporal trends in value chain structure, conduct, and performance. This paper does so.